Causes of Ineffective Electronic Journal Subscription in Academic Library - Pambayun, Kuncoro Galih (Department Library of Governance Institut of Home Affairs, 2020)
Problem Statement: The high cost of e-journal subscriptions makes it difficult for universities to have several databases for scientific disciplines. Meanwhile, database subscriptions is one of the library accreditation assessment points that create prestige for universities. Purpose: This study aims to determine the ineffectiveness of e-Journal subscriptions in the IPDN Library. Method: Method: Data were collected by interviewing 13 respondents out of a survey of 90 with the Convergent Parallel Mixed Method. The obtained data were further analyzed using a technique adapted from Sin and Kim's research, which is based on the factors influencing a person's desire to use electronic journal database facilities. This technique analyzed the readiness of human resources, infrastructure, budget, and legal protection. Result: The result showed that the librarian's human resource's support is in the very good category. Furthermore, users possess very good computer and software skills, good motivation and electronic search skills, and moderate foreign language skills. However, university libraries still lack infrastructure support due to insufficient search equipment, inadequate internet network, and limited content. Although budget support is included in the lacking category, institutional support related to the legal protection is sufficient, while sharing and using e-resources are carried out with the National Library. In addition, due to the numerous academic institutions in Asia, sharing and use of e-resources have become difficult, with poor collaborations among universities within the country. Conclusion: The causes of ineffective e-journal subscriptions are budget constraints, limited supporting devices, poor internet network, limited content, as well as lack of e-resource collaboration and sharing with other university libraries. Keywords: E-Journal Subscription; e-Resources; Library Services; Academic Library, IPDN Library